Collaborative response to arsenic-contaminated soil in an Appalachian Kentucky neighborhood. Issue 12 (18th June 2019) - Yaffee, Anna Q.; Scott, Ben; Kaelin, Colleen; Cambron, Janie; Sanderson, Wayne; Christian, W. Jay; Moran, Tim P.; Chamness, Jan
ABSTRACT: The aim of this study was to identify factors associated with an increased exposure to arsenic-contaminated soil in a Kentucky neighborhood as part of collaborative public health response. An exposure assessment survey was administered to residents and toenail clippings and soil samples analyzed for arsenic concentration. The associations between exposure variables and arsenic concentrations were evaluated using a multivariate-generalized estimating equation. An ecological assessment of cancer incidence in the community was also conducted using standardized incidence ratio maps. Median toenail arsenic was 0.48 micrograms/gram (µg/g), twice the expected regional level of 0.2 µg/g. Mean residence surface soil arsenic level was 64.8 ppm. An increase of 1 ppm of residence concentration was significantly associated with a 0.003 µg/g rise in toenail levels. Concentrations for respondents who engaged in digging were 0.68 µg/g significantly higher compared to individuals who did not. No significantly elevated rates of lung or bladder cancer were observed in the affected ZIP codes. Living in areas with high soil arsenic contamination might lead to (1) increased exposure; (2) elevated residence soil arsenic concentrations and (3) the action of digging in the soil was associated with elevated toenail arsenic levels. Based upon elevated soil levels identified, residents were recommended to move from the contaminated environment until remediation was complete. Additional recommendations included regular health-care follow-up.